Teachers’ Beliefs About Classroom-Based Assessment: Challenges And Possible Solutions For Indonesia Teachers - Kamanasa, Louisa Sarah (Loquen, 2024)
This study sought to discover the beliefs of three teachers at Maluku Barat Daya, Indonesia concerning classroom-based assessment by using descriptive qualitative approach to find out the teachers’ beliefs and its sources. This research also identifies the challenges teachers faced while putting it into practice and suggests ways they employed to get beyond those challenges. This study used a qualitative methodology and was divided into three phases for data collection: classroom observation, in-depth interviews, and document reviews. The data were triangulated to ensure validity, and Cresswell's flow model was utilized for analysis (2012). The study's findings demonstrated how crucial teachers’ opinions are regarding classroom-based assessment for individual assessments aimed at improving students' proficiency in the target language. The English Teacher Union, personal experiences, literature, lesson plans, and curriculum are the sources of the instructors' beliefs. However, when it came to putting classroom-based evaluation into practice, students' lack of skill and attitudes posed problems. Teachers address these issues by going over the content again, doing an icebreaker activity, and raising awareness of the pupils' deficiencies. This study comes to the conclusion that the phenomena in the classroom and instructors' views are related